Pulp chamber temperature changes during resin composite photoactivation - Luis Felipe Jochims Schneider; Larissa Maria Assad Cavalcante; Rubens Nisie Tango; Simonides Consani; Mário Alexandre Coelho Sinhoreti; Lourenço Correr Sobrinho (Brazilian Journal of Oral Sciences, 2015)
The aim of the present study was to verify if there is any difference in the pulp chamber temperature rise during the photo-activation of two resin composites with different viscosities. Eighteen extracted bovine incisors were divided into two groups (n=9) that were restored with two different resin composites – Filtek Z250 and Filtek Flow (3M/ESPE Dental Products, St Paul, MN 55144, USA). During the photo-activation, with a conventional halogen light curing unit (XL 2500, 3M/ESPE), a type-K thermocouple registered the temperature rise peak in the pulp chamber. The temperature rise data were submitted to Student-t test at 5% significance. The resin composite Filtek Flow shows statically higher mean temperature rise (p<0.05). We conclude that the resin composites with different viscosities produce different temperature changes during the photo-activation.